Growth and Carcass Characteristics of Beef-Cross-Dairy-Breed Heifers and Steers Born to Different Dam Breeds. - Williamson HR; Schreurs NM; Morris ST; Hickson RE (MDPI (Basel, Switzerland), 2022)
Approximately two thirds of the annual beef kill in New Zealand originates from the dairy industry. The recent increase in Jersey genetics in the dairy herd will inevitably result in an increase in Jersey genetics entering the beef herd from retention of dairy-origin calves for finishing. Limited literature is available on the effect of dam breed on the performance of beef-cross-dairy-breed progeny. The aim of this study was to investigate the effect of dam breed from dams with varying proportions of Friesian and Jersey genetics on growth traits and carcass characteristics of their 24-month-old beef-cross-dairy-breed heifer and steer progeny. Liveweights of 142 heifers and 203 steers from Friesian (F), Friesian-cross (FX), Friesian-Jersey (FJ) and Jersey-cross (JX) dams were recorded at birth, weaning, as yearlings and at slaughter. Carcass characteristics were also recorded. At each point measured, liveweight was greatest for calves born to F dams. Calves born to F dams took 93 days to reach a weaning weight of 100 kg, whereas those from FX, FJ and JX dams took 99, 101 and 102 days, respectively. Carcass weight was greatest for progeny of F dams (286 kg, compared with 279, 275 and 276 for progeny of FX, FJ and JX dams, respectively). The progeny of JX dams had yellower fat than all other dam breed groups and a greater incidence of excessively yellow fat (fat score ≥ 5).
Keywords: carcass; dairy-beef; dam; genetics; growth rate